Modern Pension Provision System as a Social Insurance Program - Rafael Y. Rakhmatullin, Rail R. Uraev, Venera F. Yunusbaeva,; Shaidukova, Liana D.; Semenova, Elvira R.; Aleksandr M. Rudakov, Albina R. Valieva, Zulfiya R. Mingazova, Liliya F. Zaynetdinova, (Opción, 2019)
The article presents the results of the author’s empirical research that is the expert survey of employees of different management levels in the field of the regional pension provision system via a systematic approach, the essence of which is to present the object of study as a system. As a result, the author gives the definition for the notion pension provision system as a social insurance program. There are also main characteristics of Russian pension provision programs. In conclusion, pension provision system is a collective work of different social institutions